Margaret Silas - Ngurumo village, Ntakira - Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2010)
Margaret Silas is a Kenyan female farmer who grows coffee, sweet potatoes, mango, macadamia, arrow roots and trees on her farm. She faces a lot of problems due to the lack of rain leading to seedlings drying out and subsequent re-plantation for the farmers. As a response, the villagers started using chemicals which lead to less produce than before. Today Margaret use conservational farming techniques on her farm, leading to higher yields and improved food security. By including more manure and making small holes for the seeds, the seeds can await the rain for up to 2 weeks. Margaret Silas explains that there is a big difference between traditional farming and conservational farming since the latter protects the soil and prevents it from eroding. She has had great success from including conservation techniques on her farm, and increasing her yields from 3-4 bags of maize, to 57 bags.